2017
DOI: 10.1123/jsr.2015-0151
|View full text |Cite
|
Sign up to set email alerts
|

Is the Combination of COL1A1 Gene Polymorphisms a Marker of Injury Risk?

Abstract: The study showed that GG homozygotes were underrepresented in the ACL-rupture group compared with the control group, which suggests an association with reduced risk of ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…By the way, there is a second COL1A1 polymorphism (COL1A1 1997G/T, rs1107946) that has been studied with the incidence of ACL injuries, whereas no significant association was identified. [ 11 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…By the way, there is a second COL1A1 polymorphism (COL1A1 1997G/T, rs1107946) that has been studied with the incidence of ACL injuries, whereas no significant association was identified. [ 11 , 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on recreational skiers who suffered ACL injury examined the association between a combination of COL1A1 gene polymorphisms and ACL lesion 17. They found that GG homozygotes were underrepresented in the ACL rupture group, suggesting an association with reduced risk of ACL injury.…”
Section: Introduction and Basic Sciencementioning
confidence: 99%
“…No statistically significant differences were found in the carrier of the studied genotypes or alleles for the carrier of SNV rs1107946 in the skiers and the control group. At the same time, the GG genotype was the most common, although its carrier did not differ statistically significantly in skiers with a cruciate ligament tear and without it [28].…”
Section: Col1a1 Genementioning
confidence: 81%
“…There are many studies that report an association of SNV in the COL1A1 gene with a predisposition to damage to muscles, tendons, and ligaments [10,28,31,32]. SNV in the COL1A1 gene can alter its expression and affect the properties of the type I collagen protein, which can subsequently increase the risk of sports injuries.…”
Section: Col1a1 Genementioning
confidence: 99%
See 1 more Smart Citation